Energy management handbook - Turner, Wayne C. (Marcel Dekker, 2005)
Building on the foundation of previous editions, recognized as the definitive stand-alone energy manager's desk reference, used by thousands of energy management professionals throughout the industry, this fifth edition includes new chapters on building commissioning and green buildings. It provides in-depth coverage of every component of energy management, including boiler and steam system optimization, lighting and electrical systems, HVAC system performance, waste heat recovery, cogeneration, thermal energy storage, energy management control systems, energy systems maintenance, industrial insulation, indoor air quality, reliability, and energy management program organization.